Concept of preschool children of their male teachers - Castillo, Al Paolo D. (College of Home Economics, University of the Philippines Diliman, 2019)
This study aims to discover how preschool children view their male preschool teachers, in light of prevailing gender-stereotypical mindsets towards males in early childhood education. In addition to this, the study seeks to determine the concepts of these children across three age groups in both sexes. To achieve this, thirty preschool children from four different preschools within Metro Manila were randomly selected for a semi-structured interview and participatory drawing. Through these methods, the participants were able to express their thoughts and experiences with their male preschool teachers. The responses were analyzed and categorized into themes found across the data. Results show that preschool children are able to view their male preschool teachers in multiple ways, and that they view their male teachers as companions, task helpers, learning guides, classroom managers and facilitators, and promoters of independence. Additionally, younger participants were shown to view their male teachers more frequently as task helpers, while the older participants view their male teachers more frequently as companions and helpers. The two sexes were shown to have little differences in their concepts of their male preschool teachers. The children were shown to describe their teachers through their environment and adult interactions. Moreover, the children did not mention the sex of their teachers to provide explanations to their answers. With these findings, the study may allow for the development of more appropriate practices, as well as a more flexible perspective on gender roles within the school and inside the family.